FUTURE TEACHERS TRAINING TO INNOVATIVE PEDAGOGICAL ACTIVITY: CONTEXT APPROACH - Shevchenko L. (Kherson State University, 2017)
The innovative processes in education arose in different historical periods and determined its development. The analysis of theoretical and experimental studies showed that now the teachers have difficulty in developing and implementing innovative technologies, choosing the most appropriate pedagogical methods and assets. The widespread innovations lead to changes in future teachers' training to the professional activity. The leading objective of higher pedagogical education is to train teacher who has the developed personal and professional skills, able to perform innovative teaching activity. The achievement of this strategic objective requires the organization of targeted training of future teachers to innovative pedagogical activity in terms of higher education system, promoting their professional and personal growth, the formation of innovative capacity and innovative culture. In this regard, there is a need to find approaches to education that are focused on the future content of professional activity. In our opinion, these requirements fully meet the contextual approach that provides consistent, continuous and systematic formation of future teachers' readiness to innovative pedagogical activity. The this article we analyzed the features of the training of future teachers to innovative pedagogical activity; identified the possibilities of contextual education application in pedagogical institutions; considered the survey results of the beginning teachers of secondary and vocational schools; defined a number of innovative forms, methods and technologies for implementing the contextual education system thet allow combining educational, quasi professional and educational-professional activity, such as: design and usage of electronic educational resources, electronic teaching methods; engaging students into self-educational activity by means of Web services; fulfillment of individual and group projects based on Web and Blog-quests in which the online learning in the context of future professional activity takes place. Examples of their development and usage in educational process are shown.